Pengaruh beberapa jenis pakan hijauan terhadap pertumbuhan ikan Koan Stenopharyngodon idella - Babo, Desmianti; Sampekalo, Julius; Pangkey, Henneke (e-Journal BUDIDAYA PERAIRAN, 2013)
The aim of this research was to determine effect of feed plants on growth of grass carp, Stenopharyngodon idella. Grass carp used had an average length of 12.8 cm and weight of 21.00 g. Fish were kept in 12 pouch nets with a density of 8 fish/net. Fish was fed in et libithum, twice a day. This research used Completely Randomized Design with four treatments: A Pennistum purpureum, B Eichornia crassipes, C Pistia stratiotes and D Azolla pinnata, each with three replications. Data from each treatment were statistically analyzed using analysis of variance and LSD. Research results showed that growth of fish in treatment C was significantly different as compared to other treatments. Length of fish reached 3.30 cm, absolute growth 22.12 g and relative growth achieved 103.60%. thus, application of feed plant Pistia stratiotes might improved growth of grass carp.